Analysis of the Influence of Work Motivation, Work Discipline and Workload on Employee Performance at PT Inticosmetic Lestari Jakarta - Prasetia, Ibellia; Ariyanto , Bintoro (Sekolah Tinggi Ilmu Ekonomi Bhakti Pembangunan, 2024)
This study aims to determine the effect of work motivation, work discipline and workload on the performance of employees of PT. Inticosmetic Lestari either partially or together. The data analysis method used is multiple linear regression analysis, analysis of the coefficient of determination, t test, and F test. Multiple linear regression analysis produces the equation Y = 3.154 + 0.248X1 + 0.448X2 – 0.231X3. The results of the t and F tests show that work motivation, work discipline and workload have a significant effect on the performance of employees of PT Inticosmetic Lestari either partially or simultanously. Work motivation and work discipline have a positive effect while workload has a negative effect on employee performance. The coefficient of determination of 0.86 indicates that the variation in employee performance is explained by the variables of work motivation, work discipline, and workload of 86%.